Badan Usaha Milik Desa dan Peningkatan Kesejahteraan Masyarakat - Windy Putri Wiratna; Rahma Rina Wijayanti (Politeknik Negeri Jember, 2023)
This research aims to clarify the role of Binor Village-Owned Enterprises, in accordance with Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises. Binor Village, Paiton District, Probolinggo Regency became the location of this research. This research is included in the category of qualitative research. The data used are both primary data and secondary data. The primary data is based on interviews while the secondary data is in the form of Binor village profiles and Binor village BUMDes profiles. The triangulation method is used to test the correctness of the data. This study uses data analysis by collecting data, reducing data, presenting data, and concluding. The Republic of Indonesia Government Regulation Number 11 of 2021 stipulates that BUMDes are established to carry out economic business activities through business management, as well as investment development, economic productivity, and village potential, which are realized through business units in BUMDes. The findings of the study show that the role of BUMDes Binor Energy has been going well, developing, and providing various benefits for the village community.